The effectiveness of Kids Song on Students’ motivation in Listening Comprehension - Sara Frimaulia (The Seall Journal, 2022)
The purpose of this study is to find out the effectiveness of Kids’ song on Students’ motivation inListening comprehension at the SDN 055999 Kw.Bingai. The importance of implementing songs inteaching English as a second language (ESL) showing that they can be very effective in developingstudent’s listening. By using kids’ song, students are expected to understand more in listening. Listening ispart of four Basic English language skills. It seems like the other skills such as writing, reading, andspeaking. These basic skills are divided into receptive skill-listening and reading- and productive skill,speaking and writing. Music and songs are crucial parts of growing and learning. There are manyadvantages to using songs in the classroom. By using kids’ song, students are expected to understand morein listening. Song are appreciated for their linguistic, cultural and entertaining features and they areprecious language learning materials. They can be used to teach and develop every aspect of language.Using songs in the learning process especially in the listening lesson it makes the students can improvetheir listening skill as one of their meaningful strategies to overcome their problem in listening skill.English song can make the students become active in the class, they are interesting, and so they can do alistening task well.